Identification of bioactive constituents of chloroform fraction from Annona muricata leaf, its antioxidant activity and inhibitory potential against carbohydrate-hydrolyzing α-amylase and α-glucosidase activities linked to type II diabetes mellitus: In vitro study - Oluwaseun Ruth Olasehinde; Olakunle Bamikole Afolabi (Shahrekord University of Medical Sciences, 2023)
Introduction: Secondary metabolites from plants have been found to play an important role in the treatment of diabetes mellitus (DM) and its complications. Therefore, the purpose of this study was to identify the chemical components of Annona muricata leaf chloroform fraction (CFAm) and its in vitro antioxidant properties, as well as inhibitory activity against α-amylase and α-glucosidase enzymatic activities. Methods: Gas chromatography-mass spectrometry (GC-MS) technique was engaged in the identification of phytochemical constituents. Antioxidant activities such as DPPH free radical scavenging ability, reducing power capacity, hydroxyl radical scavenging ability, singlet oxygen scavenging capacity, as well as α-amylase and α-glucosidase inhibition were carried out using standard in vitro methods. Results: GC-MS analysis of CFAm revealed the presence of 23 phytochemicals, out of which 5 compounds had the highest % compositions (i.e., octadecanoic acid (20.35%), 2-propanone, 1-(4-hydroxy-3-methoxyphenyl) (12.04%), isocomene (22.60%), 9, 12, 15 octadecatrienoic acid, methyl ester (Z,Z,Z) (28. 98%), and quercetin, 5TMS derivative (18.28%)). Also, CFAm demonstrated a significant (P<0.05) inhibition against DPPH (IC50= 26.33±1.39 mg/mL), with OH free radical scavenging capacity (65.46 ± 1.39 mg/100 g), singlet oxygen scavenging capacity (55.24 ± 1.22 mg/100 g), and showed ferric reducing power (84.52 ± 2.84 mg/100 g). Also, CFAm exhibited a significant (P<0.05) inhibition against α-glucosidase (IC50= 71.06 ±1.45 mg/ mL) and α-amylase (IC50= 73.88±1.58 mg/mL) in a concentration-dependent manners. Conclusion: The remarkable properties demonstrated by CFAm, which are essential for the management of DM, could probably be credited to the presence of the various identified phytonutrients.